2019
DOI: 10.1039/c9dt00770a
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced single-ion magnet behaviour of a hexacoordinated Co(ii) complex with easy-axis-type magnetic anisotropy

Abstract: This study presents the novel hexacoordinated Co(ii) mononuclear complex with SIM behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 64 publications
3
33
0
7
Order By: Relevance
“…The energies for the low-lying spin-free (δ E ) and spin-orbit (Δ E ) states, those being the energies of the terms and Kramers doublets, respectively, are given in Table 1. The six lowest in energy spinorbit states (Kramers doublets) roughly correspond to the Griffith diagram [8] at a large positive value of the axial crystal field parameter; also, the first quartet excited state is well separated from the ground one (Table 1), thus showing that the used spin-Hamiltonian description is an adequate one [29]. As can be observed, the d-orbitals splitting does not match D 4h distorted octahedral coordination; there is a strong destabilization of d z2 -orbital which is more characteristic for square planar coordination.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 81%
“…The energies for the low-lying spin-free (δ E ) and spin-orbit (Δ E ) states, those being the energies of the terms and Kramers doublets, respectively, are given in Table 1. The six lowest in energy spinorbit states (Kramers doublets) roughly correspond to the Griffith diagram [8] at a large positive value of the axial crystal field parameter; also, the first quartet excited state is well separated from the ground one (Table 1), thus showing that the used spin-Hamiltonian description is an adequate one [29]. As can be observed, the d-orbitals splitting does not match D 4h distorted octahedral coordination; there is a strong destabilization of d z2 -orbital which is more characteristic for square planar coordination.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 81%
“…2,2′-((Butane-2,3-diylidene)-bis­(hydrazin-1-yl-2-ylidene))­bis­(4,6-dimethylpyrimidine) ( L ) was synthesized, as described earlier . All other reagents and solvents were purchased from commercial sources and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we report the structure, magnetic properties, and ab initio quantum-chemical study of compound 1 in comparison with the previously reported compound 2 differing from 1 by the apical monodentate ligands.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the approaches to increase magnetic anisotropy is to use special ligands with a less-common coordination since the anisotropy depends on the coordination number of the metal centers [5,6]. The magnetic anisotropy can be improved by a rational ligand design [7][8][9][10][11][12][13][14][15]. The "ligand approach" has already led to a variety of mononuclear 3d metal ion-based SMMs (so-called single-ion magnets (SIMs)) with improved characteristics [6].…”
Section: Introductionmentioning
confidence: 99%